Thermal vacuum method for producing photoconductive CdSe films with transparent SnO2 contacts - Bakhodir K.Tuychibaev (Genius Journals, 2025)
The paper proposes a method for obtaining contacts with 70-80% transparency (at 700- 720 nm) and a resistance of 90-110 Ohms using cathodic sputtering from a mixture of SnO2 and CdO onto a glass substrate. This is done by preliminary thermal evaporation of an Sn layer onto the Cd cathode surface in high vacuum. The method for manufacturing a photosensitive CdSe film is also developed, which involves thermovacuum deposition of CdSe onto a substrate with a transparent SnO2 layer, followed by thermal treatment of the freshly prepared film in a quasi-sealed chamber in the air in the presence of CdCl2 or CuCl2 vapors, ensuring uniform diffusion of photosensitive substances.
Keywords: Thin films; photodetectors; longitudinal photoconductivity